Flowchart of DEM Modeling Stability Analysis of Large Underground Powerhouse Caverns - Tao Wang; Bowen Fan; Shyam Sundar Khadka (Advances in Civil Engineering)
The power of the Distinct Element Method (DEM) in solving the stability of underground powerhouse caverns (UPC) is discovered, but when does the DEM need to be adopted? What problems can be solved? The flowchart is provided and applied to analyze the stability of UPC in this paper. With the guide of the flowchart, the damage index (Di) is used as a failure type (gravity-controlled or stress-induced) judgment indicator. Through the calculation of three typical engineering, the problems of random blocks stability, dynamic calculation, and support system evaluation are studied, respectively, with the help of the DEM code 3DEC. The method and results of this paper can give reference to engineering projects of its category.